QUALITY OF LIFE OF PATIENTS WITH BRONCHIAL ASTHMA - Qobiljonova Sh.R.; Makhsudova S.O. (Bright Mind Publishing, 2025)
Bronchial asthma (BA) is a chronic inflammatory disease of the respiratory tract with multiple pathophysiological mechanisms leading to recurrent episodes of bronchoconstriction and structural changes in the bronchi. BA is widespread among children and adults. More than 235 million people worldwide suffer from this pathology. In the first year of life, the incidence of BA is higher in boys, in the period from 12 to 14 years, girls "catch up" with their peers in this indicator, and later women suffer more often than men. Childhood BA is a difficult to manage disease due to age-related features. It is characterized by dynamic clinical manifestations, a range of risk factors different from adults, limitations in the appointment of drug treatment and the use of functional diagnostics. Despite the introduction into practice of modern consensus documents forming the main directions of therapy and preventive measures for childhood BA, the existing insufficient level of control over the nosology determined the need to identify a new term " endotype ", which combines the genetic and epigenetic components of BA. Poor disease control, according to experts, is mainly associated with genetic characteristics, the impact of risk factors and low patient adherence to treatment. Although mild forms of BA are mainly found in the population, the greatest medical and social significance is attributed to moderate and severe forms of the disease, which is due to the serious direct and indirect economic costs associated with them due to frequent exacerbations and the presence of disabling forms.